Organizing Voices in Maine to Support Successful Aging - Wihry, David (Maine Policy Review, 2015)
David Wihry discusses the efforts of four associations in Maine that are supporting successful aging by organizing the voluntary, private, and public sectors; embracing a multidisciplinary perspective; and bringing together partners from across the state to make a larger impact on policy, attitudes about aging, and the well-being of older adults.